Antistatic and non-deformable tin-based alloy welding wire and preparation method thereof

Through the combination technology of bamboo charcoal, bentonite, urea granulation, butyl titanate and neodymium molybdenum, a tin-based alloy welding wire that is not easy to deform is formed, which solves the problem of single wire variety and insufficient anti-corrosion performance, and improves the welding wire Strength and corrosion resistance.

CN117862737BActive Publication Date: 2025-01-07李旦
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311794611.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-25
Publication Date
2025-01-07
Estimated Expiration
2043-12-25

AI Technical Summary

Technical Problem

The existing welding wire has a single variety, which is difficult to meet the needs of high strength, high toughness, and large-scale steel plate welding. Especially when steel structures in coastal areas have severe corrosion, the corrosion resistance requirements are high.

Method used

Bamboo charcoal, bentonite and urea mixed granulation to form nitrogen-doped porous microspheres, combined with butyl titanate and neodymium molybdenum plating solution for electrodeposition treatment, and after extrusion and nitriding, a tin-based alloy welding wire that is antistatic and not easily deformed is formed. .

Benefits of technology

The strength, conductivity and corrosion resistance of the welding wire are improved, and the grains are refined through carbon and nitrogen compound pinning to enhance the overall performance of the welding wire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an antistatic and non-deformable tin-based alloy welding wire and a preparation method thereof, and relates to the technical field of welding wires. The invention utilizes bentonite, bamboo charcoal, and urea to mix and granulate, sinter to form nitrogen-doped loose porous microspheres, and then utilizes the holes to adsorb butyl titanate, so that it can adhere to various phase structures in the welding wire alloy melt, interconnect with each other, and improve the strength of the welding wire. At the same time, the carbon elements and nitrogen elements in the titanium and microspheres generate carbonitride compounds, which play a pinning role on the migration of grain boundaries and subgrain boundaries, so that the grains are refined, and the strength of the welding wire is further improved; then, through extrusion and electrodeposition cycle treatment, molybdenum and neodymium metal elements penetrate into the alloy grain boundaries of the welding wire, and the electrical conductivity and corrosion resistance of the welding wire are improved. Then, through nitridation electrodeposition treatment, the metal elements on the surface of the welding wire generate a nitrogen-doped passivation film, and the corrosion resistance, strength and electrical conductivity of the welding wire are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of welding wires, in particular to an antistatic and non-deformable tin-based alloy welding wire and a preparation method thereof. Background Art

[0002] As domestic and foreign engineering machinery, coal mining machinery, marine equipment, hydropower equipment, etc. develop towards high quality, high strength, high toughness, large-scale and light weight, welding metal materials have expanded from traditional carbon steel and low alloy steel to high strength fine grain alloy. Welding wire is a metal wire welding material used as filler metal or as a conductor at the same time. In gas welding and tungsten inert gas shielded arc welding, welding wire is used as filler metal; in submerged arc welding, electroslag welding and other metallurgical gas shielded arc welding, welding wire is both filler metal and conductive electrode. At present, the variety of welding wire is single, which is far from meeting the growing demand for steel plate shielded welding.

[0003] The performance of welding wire directly affects the quality of the project using it. The corrosion of steel structures in coastal areas is relatively serious, and the requirements for the corrosion resistance of welding wire used in these equipment are correspondingly higher. Summary of the invention

[0004] The object of the present invention is to provide an antistatic and non-deformable tin-based alloy welding wire and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing an antistatic and non-deformable tin-based alloy welding wire, comprising the following preparation steps:

[0006] (1) Mix bamboo charcoal, bentonite and urea and grind them until they pass through a 100-140 mesh sieve, then add deionized water 0.1-0.3 times the mass of the bamboo charcoal, stir at 100 rpm for 1-3 h, age at room temperature for 24 h, granulate in a granulator to obtain spherical particles, dry at room temperature for 24 h, sinter at 1180-1260° C. and normal pressure for 30-50 min in a nitrogen atmosphere, and then immerse in butyl titanate ethanol solution at a material-liquid ratio of 1:10, ultrasonicate at 100 W for 30 min, and filter to obtain composite spheres;

[0007] (2) Weigh aluminum ingots, magnesium ingots, copper ingots, aluminum-iron alloys, aluminum-manganese alloys, and aluminum-tin alloys according to mass fraction, heat and melt them, and then spray them into the composite spheres. Keep them warm for 3 to 5 hours to obtain alloy melts.

[0008] (3) Casting into cast rods with a diameter of 170 mm and a length of 360 to 365 mm at a casting temperature of 725 to 755°C, a casting speed of 90 to 130 mm / min, a cooling water temperature of 10 to 20°C, and a cooling water strength of 0.05 to 0.1 MPa;

[0009] (4) Use a planer to remove the oxide scale on the surface of the cast rod to obtain a cast rod with a diameter of 164-166 mm, which is used as the working electrode, the reference electrode is a saturated calomel electrode, the counter electrode is a platinum wire electrode, and a molybdenum-neodymium plating solution is used. The deposition time is 5-40 min at 30 ° C, and then the temperature is kept at 540-555 ° C for 6-8 h, and the temperature is kept at 420-440 ° C for 2-3 h. Put it into an extruder and extrude it at 580-620 MPa. Repeat the above steps 1-2 times to obtain a base material with a diameter of 15-19 mm;

[0010] (5) The base material, platinum sheet and calomel electrode are used as the working electrode, counter electrode and reference electrode respectively. The nitriding treatment liquid is used for treatment for 2 hours, and then the welding wire is kept at 460-490℃ for 3-5 hours. The welding wire is stretched through a stretching die to obtain an antistatic and non-deformable tin-based alloy welding wire.

[0011] Furthermore, in step (1), the mass ratio of the bamboo charcoal, bentonite and urea is 35:10:10-50:25:15.

[0012] Furthermore, the particle size of the spherical particles in step (1) is 1-10 mm.

[0013] Furthermore, the mass fraction of the butyl titanate ethanol solution in step (1) is 3-10%.

[0014] Furthermore, the mass fraction of step (2) is 4.8-6.9% Sn, 0.2-1.1% Mg, 4.6-6.4% Cu, 0.10-0.35% C, 0.01-0.06% Fe, 0.15-0.26% Mn, 0.05-0.1% Ti, 0.01-0.03% N and the balance is aluminum.

[0015] Furthermore, the melting temperature in step (2) is 740-790°C.

[0016] Furthermore, the molybdenum-neodymium plating solution in step (4) includes 10-25 g / L sodium molybdate dihydrate, 8-15 g / L neodymium trichloride hexahydrate, 25-50 g / L sodium citrate, and 0.1 g / L sodium dodecyl sulfate, with a pH of 4.

[0017] Furthermore, the nitriding treatment solution in step (5) includes 0.5 mol / L potassium nitrate and 0.1 mol / L nitric acid.

[0018] Furthermore, the diameter of the antistatic and non-deformable tin-based alloy welding wire in step (5) is 2-5 mm.

[0019] Furthermore, the current density during the electrodeposition process in steps (4) and (5) is 1-5 mA / cm 2 .

[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0021] The invention utilizes bentonite, bamboo charcoal and urea to form spherical bodies. After sintering, urea decomposes to form nitrogen-containing gas, which penetrates into the interior of the bamboo charcoal along the pores of the bamboo charcoal itself to form nitrogen-doped porous microspheres. Meanwhile, during the sintering process, bentonite melts to form liquid, which infiltrates the bamboo charcoal so that the bamboo charcoal is bonded together. Combined with the pores of the bamboo charcoal itself, the interior of the microspheres is loose and porous. Then, the capillary action of the pores is used to adsorb butyl titanate, which is then sprayed into alloy melt. The loose and porous surface of the microspheres allows the nearby melt to infiltrate the melt, while the butyl titanate in the pores can adhere to the alloy. The microspheres can connect various phase structures by relying on the pores, thereby improving the strength of the welding wire. Meanwhile, the carbon and nitrogen elements in the titanium and microspheres generate carbonitrides, which play a pinning role on the migration of grain boundaries and subgrain boundaries, thereby refining the grains and further improving the strength of the welding wire.

[0022] The present invention introduces molybdenum and neodymium metal elements on the surface of the welding wire through a first electrodeposition treatment, and then undergoes extrusion and electrodeposition cycles to uniformly cover the surface. During the extrusion process, the metal elements penetrate into the alloy grain boundaries of the welding wire to form a strong bond, thereby improving the electrical conductivity and corrosion resistance of the welding wire. The welding wire is then subjected to a second electrodeposition treatment and nitridation treatment to allow NO3 adsorbed on the molybdenum-neodymium metal elements to form a strong bond with the alloy grain boundaries of the welding wire. - It is electrochemically reduced to nitrogen and reacts with metal elements to form a nitrogen-doped passivation film, which protects the welding wire matrix, reduces surface defects, and improves the corrosion resistance and conductivity of the welding wire. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0024] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the antistatic and non-deformable tin-based alloy welding wire prepared in the following examples are as follows:

[0025] High strength: Take the same size of the embodiment and the comparative example, weld two pieces of Q690 grade structural steel under a carbon dioxide atmosphere with a welding current of 200A, a welding voltage of 25V, a welding speed of 0.2m / min and a gas flow of 20L / min, and then test the mechanical properties with reference to GB / T 25774.1.

[0026] Conductivity: The same size of the embodiment and the comparative example was taken and the volume resistivity was measured using a resistivity meter.

[0027] Corrosion resistance: The same size of the embodiment and the comparative example were placed in a constant temperature and humidity chamber at a temperature of 40°C and a humidity of 60% for 168 hours to observe the surface corrosion. Example 1

[0028] (1) Bamboo charcoal, bentonite and urea were mixed and ground in a mass ratio of 35:10:10 until they passed through a 100-mesh sieve, and then deionized water (0.1 times the mass of the bamboo charcoal) was added, stirred at 100 rpm for 1 hour, aged at room temperature for 24 hours, and granulated in a granulator to obtain spherical particles with a particle size of 1 mm. After drying at room temperature for 24 hours, the particles were sintered at 1180°C and normal pressure in a nitrogen atmosphere for 30 minutes, and then immersed in a 3% mass fraction of butyl titanate ethanol solution in a material-liquid ratio of 1:10, and ultrasonicated at 100 W for 30 minutes, and filtered to obtain composite spheres;

[0029] (2) Weigh aluminum ingots, magnesium ingots, copper ingots, aluminum-iron alloy, aluminum-manganese alloy, and aluminum-tin alloy according to mass fractions of 4.8% Sn, 0.2% Mg, 4.6% Cu, 0.10% C, 0.01% Fe, 0.15% Mn, 0.05% Ti, and 0.01% N, with the balance being aluminum, heat to 740°C to melt, spray into the composite sphere, and keep warm for 3 hours to obtain alloy melt;

[0030] (3) Casting into cast rods with a diameter of 170 mm and a length of 360 mm at a casting temperature of 725°C, a casting speed of 90 mm / min, a cooling water temperature of 10°C, and a cooling water strength of 0.05 MPa;

[0031] (4) Use a planer to remove the oxide scale on the surface of the cast rod to obtain a cast rod with a diameter of 164 mm. This is used as the working electrode, the reference electrode is a saturated calomel electrode, and the counter electrode is a platinum wire electrode. Molybdenum-neodymium plating solution is used at 30°C and the current density is 1 mA / cm 2 The substrate is deposited for 5 minutes, then kept at 540°C for 6 hours, kept at 420°C for 2 hours, put into an extruder, and extruded at 580MPa. The above steps are repeated once to obtain a base material with a diameter of 15 mm. The molybdenum-neodymium plating solution includes 10 g / L sodium molybdate dihydrate, 8 g / L neodymium trichloride hexahydrate, 25 g / L sodium citrate, and 0.1 g / L sodium dodecyl sulfate, and the pH value is 4.

[0032] (5) The base material, platinum sheet and calomel electrode are used as the working electrode, counter electrode and reference electrode respectively, and the nitriding treatment solution is used, 1 mA / cm 2The nitriding treatment liquid comprises 0.5 mol / L potassium nitrate and 0.1 mol / L nitric acid. Example 2

[0033] Bamboo charcoal, bentonite and urea were mixed and ground in a mass ratio of 44:19:12 until they passed through a 120-mesh sieve, and then deionized water 0.2 times the mass of the bamboo charcoal was added, stirred at 100 rpm for 2 hours, aged at room temperature for 24 hours, and granulated in a granulator to obtain spherical particles with a particle size of 5 mm. After drying at room temperature for 24 hours, the particles were sintered at 1220°C and normal pressure in a nitrogen atmosphere for 40 minutes, and then immersed in a 6% mass fraction of butyl titanate ethanol solution in a material-liquid ratio of 1:10, and ultrasonicated at 100W for 30 minutes, and filtered to obtain a composite sphere;

[0034] (2) Weigh aluminum ingots, magnesium ingots, copper ingots, aluminum-iron alloy, aluminum-manganese alloy, and aluminum-tin alloy according to mass fractions of 5.4% Sn, 0.6% Mg, 5.5% Cu, 0.29% C, 0.03% Fe, 0.21% Mn, 0.08% Ti, and 0.02% N, with the balance being aluminum, heat to 765°C to melt, spray into the composite sphere, and keep warm for 4 hours to obtain alloy melt;

[0035] (3) Casting into cast rods with a diameter of 170 mm and a length of 362 mm at a casting temperature of 744°C, a casting speed of 110 mm / min, a cooling water temperature of 15°C, and a cooling water strength of 0.08 MPa;

[0036] (4) Use a planer to remove the oxide scale on the surface of the cast rod to obtain a cast rod with a diameter of 165 mm. This is used as the working electrode, the reference electrode is a saturated calomel electrode, the counter electrode is a platinum wire electrode, and a molybdenum-neodymium plating solution is used at 30°C and a current density of 3 mA / cm 2 The deposition time is 20 minutes, and then the temperature is kept at 548°C for 7 hours, and then at 430°C for 2.5 hours, and then the mixture is put into an extruder and extruded at 600MPa. The above steps are repeated twice to obtain a base material with a diameter of 17 mm; the molybdenum-neodymium plating solution includes 18g / L sodium molybdate dihydrate, 11g / L neodymium trichloride hexahydrate, 39g / L sodium citrate, 0.1g / L sodium dodecyl sulfate, and pH=4;

[0037] (5) The base material, platinum sheet and calomel electrode are used as the working electrode, counter electrode and reference electrode respectively, and the nitriding treatment solution is used, 3mA / cm 2 The nitriding treatment liquid comprises 0.5 mol / L potassium nitrate and 0.1 mol / L nitric acid. Example 3

[0038] (1) Bamboo charcoal, bentonite and urea were mixed and ground in a mass ratio of 50:25:15 until they passed through a 140-mesh sieve, and then deionized water (0.3 times the mass of the bamboo charcoal) was added, stirred at 100 rpm for 3 h, aged at room temperature for 24 h, and granulated in a granulator to obtain spherical particles with a particle size of 10 mm. After drying at room temperature for 24 h, the particles were sintered at 1260°C and atmospheric pressure for 50 min in a nitrogen atmosphere, and then immersed in a 10% mass fraction of butyl titanate ethanol solution in a material-liquid ratio of 1:10, and ultrasonicated at 100 W for 30 min, and filtered to obtain composite spheres;

[0039] (2) Weigh aluminum ingots, magnesium ingots, copper ingots, aluminum-iron alloy, aluminum-manganese alloy, and aluminum-tin alloy according to mass fractions of 6.9% Sn, 1.1% Mg, 6.4% Cu, 0.35% C, 0.06% Fe, 0.26% Mn, 0.1% Ti, 0.03% N, and the balance aluminum, heat to 790°C to melt, spray into the composite sphere, and keep warm for 5 hours to obtain alloy melt;

[0040] (3) Casting into cast rods with a diameter of 170 mm and a length of 365 mm at a casting temperature of 755°C, a casting speed of 130 mm / min, a cooling water temperature of 20°C, and a cooling water strength of 0.1 MPa;

[0041] (4) Use a planer to remove the oxide scale on the surface of the cast rod to obtain a cast rod with a diameter of 166 mm. This is used as the working electrode, the reference electrode is a saturated calomel electrode, the counter electrode is a platinum wire electrode, and a molybdenum-neodymium plating solution is used at 30°C and a current density of 5 mA / cm 2 The deposition time is 40 minutes, and then the temperature is kept at 555°C for 8 hours, and then kept at 440°C for 3 hours, and then put into an extruder, and extruded at 620MPa, and the above steps are repeated twice to obtain a base material with a diameter of 19mm; the molybdenum-neodymium plating solution includes 25g / L sodium molybdate dihydrate, 15g / L neodymium trichloride hexahydrate, 50g / L sodium citrate, 0.1g / L sodium dodecyl sulfate, and pH=4;

[0042] (5) The base material, platinum sheet and calomel electrode are used as the working electrode, counter electrode and reference electrode respectively, and the nitriding treatment solution is used, 5 mA / cm 2 The nitriding treatment liquid comprises 0.5 mol / L potassium nitrate and 0.1 mol / L nitric acid.

[0043] Comparative Example 1

[0044] The difference between Comparative Example 1 and Example 2 is that step (1) is different. Step (1) is changed to: bamboo charcoal and bentonite are mixed in a mass ratio of 44:19 and ground until they pass through a 120-mesh sieve, and then deionized water 0.2 times the mass of the bamboo charcoal is added, stirred at 100 rpm for 2 hours, aged at room temperature for 24 hours, and granulated in a granulator to obtain spherical particles with a particle size of 5 mm. After drying at room temperature for 24 hours, sintering at 1220° C. and normal pressure for 40 minutes in a nitrogen atmosphere, and then immersed in a 6% mass fraction of butyl titanate ethanol solution at a material-liquid ratio of 1:10, 100W ultrasonic for 30 minutes, and filtering to obtain a composite sphere; the remaining steps are the same as those in Example 2.

[0045] Comparative Example 2

[0046] The difference between Comparative Example 2 and Example 2 is that step (1) is different. Step (1) is changed to: bamboo charcoal, bentonite and urea are mixed in a mass ratio of 44:19:12 and ground until they pass through a 120-mesh sieve, and then 0.2 times the mass of bamboo charcoal is added with deionized water, stirred at 100 rpm for 2 h, aged at room temperature for 24 h, and granulated in a granulator to obtain spherical particles with a particle size of 5 mm. After drying at room temperature for 24 h, the composite sphere is sintered at 1220° C. and normal pressure for 40 min under a nitrogen atmosphere. The remaining steps are the same as those in Example 2.

[0047] Comparative Example 3

[0048] The difference between Comparative Example 3 and Example 2 is that step (4) is different. Step (4) is changed to: Use a planer to remove the oxide scale on the surface of the cast rod to obtain a cast rod with a diameter of 165 mm, which is used as the working electrode, the reference electrode is a saturated calomel electrode, the counter electrode is a platinum wire electrode, and a molybdenum-neodymium plating solution is used. The temperature is 30°C and the current density is 3 mA / cm 2 The deposition time is 20 minutes, and then the temperature is kept at 548°C for 7 hours and 430°C for 2.5 hours to obtain the base material; the molybdenum-neodymium plating solution includes 18g / L sodium molybdate dihydrate, 11g / L neodymium trichloride hexahydrate, 39g / L sodium citrate, 0.1g / L sodium dodecyl sulfate, and pH=4; the remaining steps are the same as in Example 2.

[0049] Comparative Example 4

[0050] The difference between Comparative Example 4 and Example 2 lies in step (4). Step (4) is changed to: using a planer to remove the oxide scale on the surface of the cast rod to obtain a cast rod with a diameter of 165 mm, keeping it at 548° C. for 7 h, keeping it at 430° C. for 2.5 h, putting it into an extruder, and extruding it at 600 MPa. The above steps are repeated twice to obtain a base material with a diameter of 17 mm. The remaining steps are the same as those in Example 2.

[0051] Comparative Example 5

[0052] The difference between Comparative Example 5 and Example 2 is that step (5) is different. Step (5) is changed to: keeping warm at 475° C. for 4 h, stretching through a stretching die to form an antistatic and non-deformable tin-based alloy welding wire with a diameter of 3 mm; the remaining steps are the same as those of Example 2.

[0053] Effect example

[0054] Table 1 below shows the performance analysis results of the antistatic and non-deformable tin-based alloy welding wires of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.

[0055] Table 1

[0056]

[0057] From the comparison of the experimental data of the embodiment and the comparative example, it can be found that the present invention utilizes bentonite, bamboo charcoal, and urea to mix and granulate, sinter to form nitrogen-doped loose porous microspheres, and then adsorbs butyl titanate inside the microspheres so that it can adhere to each phase structure and connect with each other, thereby improving the strength of the welding wire. At the same time, the carbon and nitrogen elements in the titanium and microspheres generate carbonitrides, which play a pinning role in the migration of grain boundaries and subgrain boundaries, thereby refining the grains and further improving the strength of the welding wire; then, through extrusion and electrodeposition cycle treatment, the molybdenum and neodymium metal elements penetrate into the alloy grain boundaries of the welding wire to form a firm bond, thereby improving the conductivity and corrosion resistance of the welding wire; then, through a second electrodeposition treatment, a nitriding treatment is performed to make the NO3 adsorbed on the molybdenum-neodymium metal element - It is electrochemically reduced to nitrogen and reacts with metal elements to form a nitrogen-doped passivation film, which protects the welding wire matrix, reduces surface defects, and improves the corrosion resistance and conductivity of the welding wire.

[0058] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing an antistatic and non-deformable tin-based alloy welding wire, characterized in that: The method comprises the following preparation steps: (1) Mix bamboo charcoal, bentonite and urea and grind them until they pass through a 100-140 mesh sieve, then add deionized water 0.1-0.3 times the mass of the bamboo charcoal, stir at 100 rpm for 1-3 h, age at room temperature for 24 h, granulate in a granulator to obtain spherical particles, dry at room temperature for 24 h, sinter at 1180-1260° C. and normal pressure for 30-50 min in a nitrogen atmosphere, and then immerse in butyl titanate ethanol solution at a material-liquid ratio of 1:10, ultrasonicate at 100 W for 30 min, and filter to obtain composite spheres; (2) Weigh aluminum ingots, magnesium ingots, copper ingots, aluminum-iron alloys, aluminum-manganese alloys, and aluminum-tin alloys according to mass fraction, heat and melt them, and then spray them into the composite spheres. Keep them warm for 3 to 5 hours to obtain alloy melts. (3) Casting into cast rods with a diameter of 170 mm and a length of 360 to 365 mm at a casting temperature of 725 to 755°C, a casting speed of 90 to 130 mm / min, a cooling water temperature of 10 to 20°C, and a cooling water strength of 0.05 to 0.1 MPa; (4) Use a planer to remove the oxide scale on the surface of the cast rod to obtain a cast rod with a diameter of 164~166mm. Use this as the working electrode, the reference electrode is a saturated calomel electrode, and the counter electrode is a platinum wire electrode. Use molybdenum-neodymium plating solution at 30℃ and a current density of 1~5mA / cm 2 The deposition time is 5-40 minutes, and then the temperature is kept at 540-555°C for 6-8 hours, and then kept at 420-440°C for 2-3 hours. The base material is put into an extruder and extruded at 580-620 MPa. The above steps are repeated 1-2 times to obtain a base material with a diameter of 15-19 mm. (5) The base material, platinum sheet and calomel electrode are used as the working electrode, counter electrode and reference electrode respectively, and the nitriding treatment solution is used. The current density is 1~5mA / cm 2 The wire is treated at 460-490℃ for 2 hours, then kept at 460-490℃ for 3-5 hours, and stretched through a stretching die to obtain an antistatic and non-deformable tin-based alloy welding wire.

2. The method for preparing an antistatic and non-deformable tin-based alloy welding wire according to claim 1, characterized in that: The mass ratio of the bamboo charcoal, bentonite and urea in step (1) is 35:10:10-50:25:

15.

3. The method for preparing an antistatic and non-deformable tin-based alloy welding wire according to claim 1, characterized in that: The particle size of the spherical particles in step (1) is 1-10 mm.

4. The method for preparing an antistatic and non-deformable tin-based alloy welding wire according to claim 1, characterized in that: The mass fraction of the butyl titanate ethanol solution in step (1) is 3-10%.

5. The method for preparing an antistatic and non-deformable tin-based alloy welding wire according to claim 1, characterized in that: The mass fraction of step (2) is 4.8-6.9% Sn, 0.2-1.1% Mg, 4.6-6.4% Cu, 0.10-0.35% C, 0.01-0.06% Fe, 0.15-0.26% Mn, 0.05-0.1% Ti, 0.01-0.03% N and the balance is aluminum.

6. The method for preparing an antistatic and non-deformable tin-based alloy welding wire according to claim 1, characterized in that: The melting temperature of step (2) is 740-790°C.

7. The method for preparing an antistatic and non-deformable tin-based alloy welding wire according to claim 1, characterized in that: The molybdenum-neodymium plating solution in step (4) includes 10-25 g / L sodium molybdate dihydrate, 8-15 g / L neodymium trichloride hexahydrate, 25-50 g / L sodium citrate, and 0.1 g / L sodium dodecyl sulfate, with a pH of 4.

8. The method for preparing an antistatic and non-deformable tin-based alloy welding wire according to claim 1, characterized in that: The nitriding treatment solution in step (5) includes 0.5 mol / L potassium nitrate and 0.1 mol / L nitric acid.

9. The method for preparing an antistatic and non-deformable tin-based alloy welding wire according to claim 1, characterized in that: The diameter of the antistatic and non-deformable tin-based alloy welding wire in step (5) is 2-5 mm.

Citation Information

Patent Citations

  • Method for manufacturing welding wires matched with 5A01 alloy thick plates

    CN103464933A

  • Stainless steel welding electrode composition

    CN103692111A